Quality of life of short-statured children born small for gestational age or idiopathic growth hormone deficiency within 1 year of growth hormone treatment - Quitmann, Julia; Bloemeke, Janika; Silva, Neuza; Bullinger, Monika; Witt, Stefanie; Akkurt, Ilker; Dunstheimer, Désirée Patricia Alexandra; Vogel, Christian; Böttcher, Volker; Kuhnle Krahl, Ursula; Bettendorf, Markus; Schönau, Eckhard; et al. (Frontiers in Pediatrics, 2019)
Aside from clinical endpoints like height gain, health-related quality of life has also become an important outcome indicator in the medical field. However, the data on short stature and health-related quality of life is inconsistent. Therefore, we examined changes in health-related quality of life in German children with idiopathic growth hormone deficiency or children born small for gestational age before and after 12 months of human growth hormone treatment. Children with idiopathic short stature without treatment served as a comparison group. At baseline, health-related quality of life data of 154 patients with idiopathic growth hormone deficiency (n = 65), born small for gestational age (n = 58) and idiopathic short stature (n = 31) and one parent each was collected. Of these, 130 completed health-related quality of life assessments after 1-year of human growth hormone treatment. Outcome measures included the Quality of Life in Short Stature Youth questionnaire, as well as clinical and sociodemographic data. Our results showed that the physical, social, and emotional health-related quality of life of children treated with human growth hormone significantly increased, while untreated patients with idiopathic short stature reported a decrease in these domains. Along with this, a statistically significant increase in height in the treated group can be observed, while the slight increase in the untreated group was not significant. In conclusion, the results showed that human growth hormone treatment may have a positive effect not only on height but also in improving patient-reported health-related quality of life of children with idiopathic growth hormone deficiency and children born small for gestational age.
Gesehen am 17.07.2019